Vocational Education for Autism Spectrum Disorder Students towards the Market Employment - Amalin Mohamad Razali, Nurul; Jambari, Hanifah; Suhairom, Nornazira (International Journal of Psychosocial Rehabilitation, 2020)
Autism is the disability of complex childhood development that is usually realized within the first three years of neurological disorders that affect the functioning of the brain. Autism problems occur without the exception of ethnicity, the level of family income, lifestyle, and education level. The case study attempts to explore the knowledge and skills provided by private institutions to Autism Spectrum Disorder (ASD) students before they enter the job market. Five teachers at private institutions of vocational education were interviewed using a set of interview protocols. The interviewed teacher has over five years of teaching experience with ASD students. The interview data obtained was transcribed in verbatim form. Keywords or phrases have been extracted, grouped, and translated in the form of a theme. The themes are the basic skills, job-related skills, and personal qualities. The findings show that teachers have applied the ability to work (marketability) to ASD students. This study has implications for the provision of appropriate workability capability based on the strengths and abilities of ASD students.